Rock engravings marking the Redan landscape in Gauteng, South Africa - Claudia Gouws (Contree, 2024)
The ontological1 and epistemological2 foundations of reality, myths, beliefs, and practices in ritual behaviour have long been studied by scholars around the globe. There is no single understanding and representation of reality, as all that is real or existent within the universe is historically shaped by interdependent cultural and social processes and fear factors. Although the study of rock art is primary a branch of archaeology, cultural history also focuses on a past time and place, to study beliefs and ideas from a bottom-up approach and include the objects and experiences (sometimes unwritten) of the everyday life of the uneducated and less privileged. It is particularly well equipped to offer an understanding of the San myths, beliefs, ritual practices, and modes of representation of reality, as represented in their rock art. The Redan open-air rock engraving site is located on the Kookfontein farm, near the former Klip power station at Redan, close to a wetland that was formerly a rivulet that founded its way to the Klip River, a tributary of the Vaal River. The Klip-Vaal area is situated in the southern part of Gauteng, South Africa. Being part of the Late Stone Age hunting, domestic and ritual sites of the San people and later migrants it contains numerous documented and undocumented rock art sites. In line with interpretivism, the methodology is based on published and unpublished literature, as well as several on-site inspections of the site between 2002 and 2022. Authorship of the engravings at the Redan site is unconfirmed, although two dominant views regarding the cultural origin have emerged, namely a San hunter-gatherer shamanistic approach and the Koranna-Khoekhoen initiation site hypothesis.